Analysis Of Product Quality And Promotion Towards Consumer Loyalty Mediated By Consumer Satisfaction (Case Study Of Two Binjai Burger) - Isnan sarwo prasetyo; Toyib Daulay; Sri Rahayu; Elfitra Desy Surya; Nur Afrina Siregar (Yayasan Multidimensi Kreatif, 2023)
This research aims to test and analyze product quality and promotion on consumer loyalty which is mediated by Dua Burger Binjai consumer satisfaction. Consumer loyalty is an important aspect, so efforts are needed to increase customer loyalty by using several supporting aspects such as product quality, promotions, and consumer satisfaction. This type of research is quantitative research. The population in this research is Dua Burger consumers. The number of samples used in this research was 150 samples. The data analysis method used in this research uses the Structural Equation Model Partial Least Square (SEM-PLS). The results of this research are that product quality has a positive and significant effect on consumer satisfaction. Promotion has a positive and significant effect on Consumer Satisfaction. Consumer Satisfaction has a positive and significant effect on Consumer Loyalty. Product quality has a positive and significant effect on consumer loyalty. The promotion has a positive and significant effect on consumer loyalty. Product Quality has a positive and significant effect on Consumer Loyalty through Consumer Satisfaction. Promotion has a positive and significant effect on Consumer Loyalty through Consumer Satisfaction. Product Quality and Promotion have a positive and significant effect on Consumer Loyalty through Consumer Satisfaction.